Children’s religious education with reference to freedom of manifestation of belief in the European Union - Mert, Sevim Tuba (My University, 2022)
Hukuki bir perspektiften bakıldığında, çocukların dini eğitimi, çocukların ve ebeveynlerin haklarının birleşme noktası olarak değerlendirilebilir. Çocukların dini eğitimi bir yanda çocukların din özgürlüklerini ve eğitim haklarını, bir yandan da ebeveynlerin, hem kendi din özgürlükleri kapsamında inançlarını açıklama özgürlüklerini, hem de çocuklarının eğitiminde inançlarına saygı duyulmasına yönelik haklarını ilgilendirmektedir. Bu haklar, çeşitli hukuki metinlerle koruma altına alınmıştır. Bu çalışma, Avrupa Birliği hukukunda, çocukların dini eğitimi kapsamında, çocuk haklarını ve ebeveynlerin haklarını incelemeyi amaçlamaktadır. Bu amaçla, çalışmanın ilk bölümü ―çocuk‖ ve ―din‖ terimlerini, bu terimlere atfedilen hukuki korumanın kapsamını ve inanç açıklamasının görünümlerini içermektedir. İkinci bölümde ebeveynlerin ilgili haklarının çocukların dini eğitimi kapsamında sınırları ve çocukların dini eğitiminin ilgili temel haklarla ilişkisi tartışılacaktır. Son bölümde ise çocukların din eğitimiyle ilişkili haklar, din ve inanç özgürlüğü ve eğitim hakkı, Avrupa Birliği Temel Haklar Şartı, Avrupa İnsan Hakları Sözleşmesi ve Birleşmiş Milletler Çocuk Hakları Konvansiyonu kapsamında incelenecektir.

From a legal point of view, religious education of children is the confluence point of the rights of children and parental rights. It concerns the freedom of the religion or belief and the right to education of the child on one side and freedom of manifestation of belief of parents under the freedom of religion or belief and the parental rights to ensure the respect to religious convictions of parents in the education of their children on the other side. These rights are guaranteed in various legal documents. This study will analyze rights of children and parental rights in the context of religious education of children in the European Union law. For that purpose, in the first chapter, the term ―child‖, ―religion‖ and the scope of the legal protection attributed to it and different forms of manifestation of belief will be covered. Second chapter will focus on the limitations to parental rights in the scope of the religious education of children and the relationship between religious education of children and related fundamental rights. In the last chapter, the rights which concerns religious education of children; freedom of religion and right to education are discussed within the scope of the Charter of Fundamental Rights of the Union, European Convention for the Protection of Human Rights and Fundamental Freedoms and the Convention on the Rights of the Child.
Keywords: Avrupa Birliği; Avrupa Birliği hukuku; Children; çocuk hakları; Çocuklar; Din; dini eğitim; ebeveyn hakları European Union law; Education; Eğitim; European Union; fundamental rights; Hukuk; Law; parental rights; Religion; religious education; rights of the child; temel haklar